Behavior problems and children’s academic achievement: A test of growth-curve models with gender and racial differences - Kremer, Kristen P. (Child Youth Serv Rev, 2016)
The aim of this study was to examine the longitudinal association between externalizing and internalizing behavior and children’s academic achievement, particularly in terms of whether these variables varied as a function of gender and race. Data pertaining to externalizing and internalizing behavior, academic achievement, gender, and race from three waves of the Child Development Supplement of the Panel Study of Income Dynamics (N = 2028) were used. Results indicate that behavior problems had a negative relationship with academic performance and some of these associations endured over time. Externalizing behavior impacted reading scores more negatively for females compared to males at baseline, but the impact of externalizing behavior on long-term reading outcomes did not vary by gender. Externalizing behavior impacted reading scores more negatively for Black children than White children at multiple points in time. Differences between males, females, Black, and White children concerning behavior and achievement are explained. Implications, limitations, and ideas for future research are also presented.